Estudio de las sustancias giberelinoides en semillas maduras y plantas normales y enanas de frijol (Phaseolus vulgaris L.) var. México-80 R - Proaño Salas, Víctor (IICA, San José (Costa Rica), 2014)
Tesis (Mag. Sc.) -- IICA, San José (Costa Rica), 1967